Tinjauan Tematis Alquran Tentang Akal - Yuzaidi Yuzaidi; Winda Sari (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
This article discusses reason in the concept of the Koran. 'Aql in the Qur'an repeats as many as 49 times, except for one, all come in the form of fi'il mudhari', especially the material that continues with wawu jama'ah. Like the form of ta'qilun or ya'qilun. The verb ta'qilun is repeated 24 times and the verb ya'qilun is 22 times. Whereas, the verbs' aqala, na'qilu, and ya'qilu each have one time. From a number of verses of the Qur'an it can be understood that, reason has several meanings, including the power to understand and describe something, moral drive and power to take lessons and conclusions and wisdom.